2022
DOI: 10.3389/fpubh.2022.862219
|View full text |Cite
|
Sign up to set email alerts
|

Health Status and Association With Interpersonal Relationships Among Chinese Children From Urban Migrant to Rural Left-Behind

Abstract: BackgroundTo date, numerous studies have examined the health status of Chinese left-behind children and migrant children. However, the impact of children's diverse migration/left-behind experiences on their health is still unclear.MethodsA cross-sectional survey was conducted in 2020 in Nanling country (Anhui province) and Kaihua country (Zhejiang province) in China. School children from grade 5 to 8 reported their socio-demographic, interpersonal relationships, self-rated health, suicidal ideation, and depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 55 publications
1
9
0
Order By: Relevance
“…In a study conducted by Felllmeth et al, LBC had an increased risk of depression, suicidal ideation, and anxiety (Fellmeth et al, 2018). That LBC are more likely to experience depressive symptoms and suicidal ideation is supported by other studies (He et al, 2012, Liang et al, 2017Zhao et al, 2022). LBC are significantly more prone to problems when it comes to mental health, which includes emotional and behavioral issues and hyperactivity (Wang et al, 2019).…”
Section: Mental Health Of Lbcmentioning
confidence: 85%
See 2 more Smart Citations
“…In a study conducted by Felllmeth et al, LBC had an increased risk of depression, suicidal ideation, and anxiety (Fellmeth et al, 2018). That LBC are more likely to experience depressive symptoms and suicidal ideation is supported by other studies (He et al, 2012, Liang et al, 2017Zhao et al, 2022). LBC are significantly more prone to problems when it comes to mental health, which includes emotional and behavioral issues and hyperactivity (Wang et al, 2019).…”
Section: Mental Health Of Lbcmentioning
confidence: 85%
“…It was also found that, among the LBC, increased issues in parental communication correlates strongly to emotional and behavioral difficulties including hyperactivity (Wang et al, 2019). Zhao et al further confirmed that maternal communication difficulty for LBC had negative association with selfreported health and positive association with intention to commit suicide and depression (Zhao et al, 2022). In addition to parent-child communication, LBC are more likely to engage in deviant peer affiliation (Yang et al, 2021), which is shown to be a strong predictor of antisocial behavior (Lee, 2011).…”
Section: Interpersonal Relationships Of Lbc and Lonelinessmentioning
confidence: 89%
See 1 more Smart Citation
“…Individuals will have different views on information disclosure under different health conditions ( 38 ). The extent to which perceived behavior has control on opt-in decisions may vary depending on the current health status of people.…”
Section: Hypothesesmentioning
confidence: 99%
“…On the one hand, the special family environment of migrant children makes their parents not have too much energy and ability to devote themselves to their children’s learning. On the other hand, the school environment of migrant children, especially those who have just transferred to city learning and have to accommodate urban style of living, is not ideal (Zhao et al, 2022). Their original close peer relationship and teacher-student relationship no longer exist.…”
Section: Introductionmentioning
confidence: 99%